Utilização da técnica de imuno-histoquímica para confirmar casos de pitiose cutânea equina diagnosticados por meio de caracterização clínica e avaliação histopatológica - Dória, R. G.S.; Freitas, S. H. [UNESP]; Mendonça, F. S.; Arruda, L. P.; Boabaid, F. M.; Martins Filho, A.; Colodel, E. M.; Valadão, C. A.A. [UNESP] (FapUNIFESP (SciELO), 2014)
Twelve granulomatous lesions in the thoracic and pelvic limbs of horses from pantaneira breed were evaluated. It was performed suggestive diagnostic of cutaneous pythiosis according to the clinic characteristics of the lesions and histopathological exams using hematoxylin and eosin (HE) and Grocott's methenamine silver (GMS) stains. The confirmation of the diagnoses was performed by the labelled streptavidin biotin (LSAB) method (immunohistochemistry). Extensive focal pyogranulomatous dermatitis associated with pseudo hyphae characteristic of Pythium insidiosum (subcutaneous pythiosis) was the histopathological diagnosis for all 12 horses used in this study. It was confirmed in 100% of the cases by the positive result to Pythium insidiosum in the immunohistochemistry exam, characterized by the visualization of branched and septated structures. It was observed 100% of parity between the techniques. We can conclude that clinical characterization of the granulomatous lesions with pythiosis aspects in horses associated with histopathology suggestive of equine pythiosis constitute a reliable method of diagnostic that can be confirmed by immunohistochemistry technique.
Immunohistochemistry analysis to confirm cases of cutaneous pythiosis in horses diagnosed by means of clinic characterization and histopathologic evaluation
Keywords: Histopathology; Horses; Immunohistochemistry; Pythiosis